IDENTIFIKASI DAN PENENTUAN PRODUK UNGGULAN DAERAH KABUPATEN KOTAWARINGIN TIMUR - Maria Christina Yuli Pratiwi (Jurnal Kebijakan Pembangunan Daerah, 2024)
East Kotawaringin Regency is one of the autonomous regions that has abundant natural resources such as oil palm, rubber, and coconut. Unfortunately, the local government has yet to establish any regional flagship products so that these commodities have not been optimally utilized. This study aims to identify and analyze flagship sectors and subsectors, flagship commodities and products that have the potential to become flagship items, as well as design strategies the development of regional flagship products. This research addresses these problems using analysis of LQ, Shift Share, MRP, Overlay, AHP, and SWOT. By using a descriptive quantitative approach, the result of the research shows that the agriculture and fisheries sector is one of superior sectors that have competitive competitiveness, meanwhile, the agriculture, livestock, hunting, and agricultural services subsector is classified as a leading subsector. Identification of potential commodities using methods of Specialization Quotient (KS) and Localization Quotient (KL) shows that superior commodities is cassava commodity. Meanwhile, the result of identification towards potential products is obtained that pure coffee and ginger coffee, also rice of siam epang are proposed to be designated as Regional Flagship Products in 2022. The strategies for developing superior products include: (1) Improving the quality of creative and innovative business actors; (2) Improving the quality of infrastructure (production); (3) Improving the quality of products promotion and investment; (4) Increasing collaboration with stakeholders; and (5) Increasing protection of regional superior products.